2022
DOI: 10.3390/ijerph191710669
|View full text |Cite
|
Sign up to set email alerts
|

Ergonomic Improvements to Agricultural Harvest Baskets to Reduce the Risk of Musculoskeletal Disorders among Farmers

Abstract: Typical harvesting baskets (TB) are used in various agricultural workplaces; however, no study to date has reported their effect on the musculoskeletal system. Therefore, this study aimed to evaluate the effects of a novel basket with attached rotational handles (RHB) to help alleviate the work-related physical burden of farmers. We analyzed the surface electromyograms (EMGs) of seven muscles, evaluated the subjective discomfort levels and locally perceived discomfort (LPD) scores to investigate the discomfort… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…In this study, the sEMG electromyographic examination showed a significant increase in muscle activation in SH_LX, SH_RX, BL_LX, and BK_RX as the display positioning angle increased (30 • > 50 • > 80 • ). The use of sEMG has been used in previous studies in the agricultural field to study muscle activation through a non-invasive procedure [11,21,22]. In this case, the increase in the positioning angle of the display caused the rotation of the head, which led to a postural alteration.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, the sEMG electromyographic examination showed a significant increase in muscle activation in SH_LX, SH_RX, BL_LX, and BK_RX as the display positioning angle increased (30 • > 50 • > 80 • ). The use of sEMG has been used in previous studies in the agricultural field to study muscle activation through a non-invasive procedure [11,21,22]. In this case, the increase in the positioning angle of the display caused the rotation of the head, which led to a postural alteration.…”
Section: Discussionmentioning
confidence: 99%
“…Work may be required [54]. Research conducted by [60] aimed to improve the ergonomics of agricultural harvest baskets can reduce the risk of musculoskeletal disorders (MSDs) among farmers in Korea. The design of Korean melon harvesting equipment was made by taking into account the product's physical characteristics and the workers' anthropometry.…”
Section: Implications Of the Findingsmentioning
confidence: 99%